Biogenic Synthesis of MnO2 Nanoparticles With Leaf Extract of Viola betonicifolia for Enhanced Antioxidant, Antimicrobial, Cytotoxic, and Biocompatible Applications - Lu, Haibin; Zhang, Xueyang; Khan, Shakeel Ahmad; Li, Wenqiang; Wan, Lei (Frontiers in Microbiology, 2021)
In this study, we propose to synthesize NPs using plant extract containing active biomedical components, with the goal of obtaining NPs that inherit the biomedical activities of the plant. Herein, we report the synthesis of manganese dioxide nanoparticles (VBLE-MnO2 NPs) using the leaves extract of Viola betonicifolia, in which the plant's secondary metabolites function as both reducing and capping agents. The synthesized NPs were successfully characterized with different spectroscopic techniques. The antibacterial, antifungal, and biofilm inhibition properties of the synthesized VBLE-MnO2 NPs were further explored against a variety of bacteria (Gram-positive and Gram-negative) and mycological species. Additionally, their antioxidant ability against linoleic acid peroxidation inhibition, cytobiocompatibility with hMSC cells and cytotoxicity against MCF-7 cells were investigated compared to leaves extract and chemically synthesized manganese dioxide NPs (CH-MnO2 NPs). The results were demonstrated that the synthesized VBLE-MnO2 NPs presented excellent antibacterial, antifungal, and biofilm inhibition performance against all the tested microbial species compared to plant leaves extract and CH-MnO2 NPs. Moreover, they also exhibited significant antioxidant potential, which was comparable to the external standard (ascorbic acid); however, it was higher than plant leaves extract and CH-MnO2 NPs. Furthermore, the synthesized CH-MnO2 NPs displayed good cytobiocompatibility with hMSC cells compared to CH-MnO2 NPs. The enhanced antioxidant, antibacterial, antifungal, and biofilm inhibition efficacy as compared to CH-MnO2 NPs might be attributed to the synergistic effect of the VBLE-MnO2 NPs' physical properties and the adsorbed biologically active phytomolecules from the leaves extract of Viola betonicifolia on their surface. Thus, our study establishes a novel ecologically acceptable route for nanomaterials' fabrication with increased and/or extra medicinal functions derived from their herbal origins.